PENGARUH MANAJEMEN LABA DAN CORPORATE GOVERNANCE TERHADAP KECURANGAN LAPORAN KEUANGAN - Kurniawan, Alam Ashari; Hutadjulu, Linda Y.; Simanjuntak, Aaron M. A (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2020)
This study aims to analyze the influence of earnings management and corporate governance onÂ fraudulent financial statements. This research was conducted again to review the influence of earningsÂ management and corporate governance on fraud. The population in this study is a manufacturing company listed on the Indonesian stock exchange. Based on the purposive samplingÂ method obtained by 50 companies. The number ofobservations is 150 observations. The analysis usedÂ is logistic regression. The results in this study indicate that earnings management as measured byÂ discretionary accruals and unexpected revenue per employee proves that there is no influence on fraudulent financial statements. Corporate governance as measured by managerial ownership,Â institutional ownership, board of commissioners, independent commissioners, independent auditÂ committees does not affect on fraudulent financial statements.